Sexual Assaults: A Pakistani Women and Sexual Harassments in Universities and Recent Scandal of Islamia University of Bahawalpur - Muhammad Asad Latif (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
Without a doubt, human beings are viewed more favorably by educational pedagogy as educated individuals than stupid ones. The educational system makes a distinction between humans and other animals and portrays humans as noble beings. In an Islamic climate where, serious scandals are occurring daily, it has become very challenging. According to Pakistani media, Islamia University, Bahawalpur, Pakistan reported 5500,5400 or maybe 400 obscene video records of dormitory ladies during the time of July 2023. The largest example of sexual exploitation in Pakistan to date is the one involving Islamia University. An earlier event of a such nature at Gomal University in Dera Ismail Khan resulted in the professor's honorable release. According to media reports, the vice chancellor of IUB was only forced to quit because to this incident. Although the Crime Bureau's assessment claims that there is no origin and not even one, chaos quickly spread throughout Pakistan.